2003
DOI: 10.1021/jm030180y
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Interactions of Phosphosulfomannans with Angiogenic Growth Factors by Surface Plasmon Resonance

Abstract: The binding interactions of the phosphosulfomannan anticancer agent PI-88 (1) with the angiogenic growth factors FGF-1, FGF-2, and VEGF were studied by surface plasmon resonance (SPR) on a BIAcore 3000 biosensor. Compared with heparin, PI-88 has at least 11-fold higher affinity for FGF-1 and at least 3-fold higher affinity for VEGF, but at least 13-fold lower affinity for FGF-2. To define the structural features of PI-88 that are important for growth factor binding, several analogues, such as dephosphorylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 41 publications
5
89
0
Order By: Relevance
“…PI-88, however, has a second function, since in addition to inhibiting heparanase activity, this HS mimic can directly bind to HS-binding proteins, thereby impairing their function Cochran et al, 2003;Francis et al, 2003;Khachigian and Parish, 2004). Thus, the angiogenesis inhibition that we observe in vivo may reflect both of these mechanisms, each serving the same outcome: namely, to limit the bioavailability of HS-binding growth factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI-88, however, has a second function, since in addition to inhibiting heparanase activity, this HS mimic can directly bind to HS-binding proteins, thereby impairing their function Cochran et al, 2003;Francis et al, 2003;Khachigian and Parish, 2004). Thus, the angiogenesis inhibition that we observe in vivo may reflect both of these mechanisms, each serving the same outcome: namely, to limit the bioavailability of HS-binding growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…PI-88 acts as a noncleavable structural mimetic of HS, occupying the active site of heparanase, thus inhibiting heparanase cleavage of endogenous HS chains. PI-88 has the additional property of directly binding to heparin-binding regulatory factors Cochran et al, 2003;Francis et al, 2003;Khachigian and Parish, 2004), potentially perturbing downstream signaling via their receptors (Ornitz, 2000;Powers et al, 2000). Both of these effects appear to be relatively specific, in that related oligosaccharides of different lengths and/or number of sulfated residues were not as potent as PI-88 in inhibiting heparanase activity, angiogenesis, or metastasis , indicating that PI-88's Angiogenic switching in progenitor lesions RIP1-Tag2 mice were treated with PI-88 at two different doses, 30 or 60 mg/kg/day, in three separate trials that target different stages in tumorigenesis (Bergers et al, 1999).…”
Section: Characterization Of Heparanase Levels During Multistep Tumormentioning
confidence: 99%
“…As our identified Hh GAG-binding site resides at a Hh receptor-binding region, our Shh-GAG structures might form a platform for the rational design of GAG mimetics as a unique class of Hh pathway modulators. Similar strategies focused on other morphogen signaling systems, for example, the signaling modulator PI-88, a HS mimetic, can specifically modulate the interactions of fibroblast growth factor (FGF) and its receptor (FGFR) (38). FGF-FGFR interactions are heparin dependent and require simultaneous binding of FGF and heparin to form a ternary signaling complex (39,40), analogous to the fHh-Ihog-heparin complex (31).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have demonstrated that PI-88 directly binds to FGF-1, FGF-2, and VEGF. In addition, FGF-2 binding by PI-88 renders it biologically inactive (26,27). PI-88 has been likened to a heparan sulfate mimetic acting by simply sequestering released growth factors and rendering them biologically inactive (28).…”
mentioning
confidence: 99%